A computational-cum-experimental study provides some clues on the druggable binding site and design of anticancer therapeutics on ETV1 transcription factor oncoprotein. Issue 11 (11th August 2021) - I.V, Ambily Nath; A, Jero Mathu; A, Jayakumaran Nair; Nair, Achuthsankar S.
Abstract : Triprolidine docking to each of the five single-residue ETV1 mutants featured Met424 and Cys416 as hot spots that rendered a logically correct high affinity pose. This reshaping of the dimer interface could guide the design of anticancer compounds. Abstract : The past few years have seen many advances in the discovery of E26 transformation-specific sequence variant 1 (ETV1)-targeted anticancer compounds. Small molecular transcriptional regulation of ETV1 has successfully impeded malignant tumors. Even so, its structural and therapeutic features remain obscure. On this note, the present computational- cum -experimental study was carried out. We used factual data and predictions to derive a rational inference that the ETV1 dimer interface is the druggable binding site and this hydrophobic surface may pick non-polar ligands. This hypothesis was proved by the MTT assay of phytochemical hits from our previous work. CID5282443 (triprolidine) showed an IC50 of 269.56 μg ml −1 against MCF-7 and this 2-[1-( p -tolyl)-3-pyrrolidin-1-yl-propyl]pyridine was a fresh scaffold. In succeeding in silico alanine scanning, triprolidine-binding interfacial residues with preferred interaction energy cutoffs were chosen for mutation. Alanine substitution in Leu421, Met424, Phe414, Cys416, and Trp338 destabilized the protein. This correlated to their unfavorable high energy zones in residues 349–369 (310, β1, and β2), at the roof of the interface. The protein models of these five individual variants were built; Glu362, Phe363 (β2), and Tyr412 (β3) were defined as the stabilization centers with Glu362 being common to all. The pharmacological behavior of the mutants was assessed by triprolidine docking. An improved binding profile was observed for Met424A and Cys416A while Trp338A, Phe414A, and Leu421A rendered a logically incorrect ligand pose. These results and observations could set the scene for the development of potent anticancer therapeutics by targeting and reshaping the dimer interface.